Pacing in swimming: A systematic review - McGibbon, K. E.; Pyne, D. B.; Shephard, M. E.; Thompson, K. G. (Sports Medicine, 2018)
Pacing strategy, or how energy is distributed during exercise, can substantially impact athletic performance and is considered crucial for optimal performance in many sports. This is particularly true in swimming given the highly resistive properties of water and low mechanical efficiency of the swimming action. Objectives